Macrophages in Ischemic Heart Failure: Yesterday, Today, and Tomorrow. Issue 2 (6th June 2021) - Liu, Demin; Yan, Wenjun; Huang, Jingwen; Zhao, Jianli; Kilby, Houston; Christopher, Theodore A.; Lopez, Bernard; Tao, Ling; Ma, Xinliang; Gu, Guoqiang; Wang, Yajing
Abstract : Abstract: With continually improving reperfusion strategies and patient care, the overall mortality of acute myocardial infarction (AMI) has been significantly reduced during the past two decades. However, this success is a double-edged sword, as many patients surviving an AMI will progress towards ischemic heart failure (HF) over time. The pathologic causes of ischemic HF are undoubtedly multifactorial. However, the inflammatory response is considered one of the most important causes of pathological remodeling because it spans the whole process of HF development. The macrophage-mediated inflammatory response was once considered a purely harmful factor leading to pathological remodeling and HF. However, growing evidence demonstrates that multiple subgroups of macrophage exist and contribute differently to ischemic HF development. Understanding macrophage populations and how they contribute to post-MI remodeling and consequent ischemic HF is, therefore, critical to understanding and treating the disease. This review focuses on different macrophage populations that regulate post-MI cardiac injury and how immunoregulation therapy may benefit patients with ischemic HF.